2018
DOI: 10.1097/mpg.0000000000002019
|View full text |Cite
|
Sign up to set email alerts
|

The Esophageal‐Atresia‐Quality‐of‐life Questionnaires

Abstract: The overall psychometric performance of the EA-QOL-questionnaires for EA/TEF children is satisfactory and can enhance outcome evaluations in future research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(90 citation statements)
references
References 42 publications
1
78
5
Order By: Relevance
“…The study was a part of a Swedish-German project focusing on HRQOL in children and adolescents born with EA and their families, 9,[15][16][17] and was approved by the Ethical Review Boards of Gothenburg, Sweden (DNR 958-13) and Hannover, Germany (2936-2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study was a part of a Swedish-German project focusing on HRQOL in children and adolescents born with EA and their families, 9,[15][16][17] and was approved by the Ethical Review Boards of Gothenburg, Sweden (DNR 958-13) and Hannover, Germany (2936-2015).…”
Section: Methodsmentioning
confidence: 99%
“…10 In recent years, condition-specific HRQOL instruments have been developed and validated for EA patients aged 2 to 7 and 8 to 17 years. [15][16][17] These instruments evaluate the age-specific HRQOL domains as presented in ►Fig. 1.…”
Section: Introductionmentioning
confidence: 99%
“…Information is obtained from multidimensional general or condition-specific questionnaires that integrate aspects from a physical, social, psychological, and emotional perspective. [44][45][46] While in the past condition-specific HRQoL instruments have been developed and validated for children with EA, [47][48][49] the use of general instruments has been more common, as these allow for comparison to a variety of populations, for example, a healthy control group. 44 The validated questionnaires used to assess the patient's subjective perception of health were: the KIDSCREEN-27, 50,51 the Gastrointestinal Quality of Life Index (GIQLI) 52,53 , and the World Health Organization (WHO)-5 questionnaire.…”
Section: Data Collectionmentioning
confidence: 99%
“…Esophageal atresia (EA) is a rare malformation occurring in 2.4/10 000 births. While survival rates today exceed 90%, long-term esophageal and respiratory sequelae remain common (Dellenmark-Blom et al, 2018). Although neonatal survival is no longer a problem, there is scarce data about the patients' long-term outcomes, including health-related quality of life (HRQOL) (Legrand et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Only one study examined differences in children's self-reports and parent proxy-reports in children with EA, which showed satisfactory agreement, but with varying results depending on the investigated HRQoL domain (Dellenmark-Blom et al, 2018;Flieder et al, 2018). However studies have shown that parents of children with chronic diseases tend to score their children's HRQOL lower than the children (She er, Hanley, Bagley, Molitor, & James, 2009), the reliability of using parent proxy-reports has been questioned (Panepinto, Hoffmann, & Pajewski, 2010).…”
Section: Introductionmentioning
confidence: 99%